The Role and Challenges of Women in Realizing Harmonious Families Towards Society Era 5.0 from an Islamic Law Perspective - Distiliana Distiliana; Herlinsi Herlinsi (CV Media Inti Teknologi, 2024)
This study aims to determine the Role and Challenges of Women in Realizing a Harmonious Family towards Society era 5.0. This research is descriptive qualitative research with the type or nature of literature research or literature research, as for the technique used, namely, researchers collect data related to research in the form of books, manuscripts, articles, previous research reports, and newspapers both online and offline and so on. The research results showed that women are creatures created by God (Allah) who have the nature of menstruation, pregnancy, childbirth, and adjustment. Society 5.0 is a concept of changing social, economic, and educational life in the digital era, where almost all human work will be replaced by machines. The roles and challenges of women in realizing a harmonious family towards Society 5.0 are life changes, managing households, educating children, supporting husbands' work, and fighting for gender equality. The challenge is the role—double, gender inequality, work-family balance, unfettered internet access, and changing values and morals.